(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper examines the novel shiva Trilogy including all the three sections composed by Amish Tripathi. Mythology has been an unavoidable source and subject of concentrate in writing down the ages. The authors since numerous ages have attempted to re-decipher the previous fantasies. The aim here is to give another point of view to the since a long time ago established fantasies of the hundreds of years. Amish Tripathi, as the grandson of a Sanskrit researcher and Pandit in Benaras, revered ladies legendary characters in his Shiva Trilogy. He materializes power and flame from his ladies characters contrasting with male counterparts. The research paper explores Amish Tripathi position in this deep rooted practice in a bigger range and his contribution to Indian Writing in English. Further, it comprises of close textual analysis of Shiva Trilogy with reference to the act of retelling of Indian mythology.